Decision Support System Using the SAW Method for Determining Research Priorities at Universitas Islam Kuantan Singingi - Aprizal; Febri Haswan; Nofri Wandi Al-Hafiz; Harianja; Gunardi Hamza (P3M Politeknik Negeri Bengkalis, 2025)
Universitas Islam Kuantan Singingi receives numerous research proposals from lecturers every year. Limited resources, such as funding, facilities, and expertise, mean that not all proposals can be funded. Therefore, a selection process is necessary to determine which research is eligible for funding. Currently, selection is still carried out conventionally, which is time-consuming and potentially subjectivist, especially in determining the importance of criteria. To address these issues, a Decision Support System was developed using the Fuzzy Multiple Attribute Decision Making method using the Simple Additive Weighting approach. This method is capable of processing various assessment criteria to produce objective weights, values, and rankings for each research proposal. The system's calculations are expected to provide recommendations for priority research as a basis for granting grants at Kuantan Singingi Islamic University. Thus, this system assists the LPPM-DI Universitas Islam Kuantan Singingi in distributing research grants more quickly, transparently, and accurately.